Trunk balance, head posture and plantar pressure in adolescent idiopathic scoliosis - Wen, Jin-Xu; Yang, Hui-Hui; Han, Shu-Man; Cao, Lei; Wu, Hui-Zhao; Yang, Chen; Li, Han; Chen, Lin-Lin; Li, Nuan-Nuan; Yu, Bao-Hai; Gao, Bu-Lang; Wu, Wen-Juan (Frontiers in Pediatrics, 2022)
Background: The relationship of trunk balance with head posture and plantar pressure is unknown in patients with adolescent idiopathic scoliosis (AIS). Objective: To investigate the relationship of trunk balance with head posture and plantar pressure by analyzing the imaging data of patients with AIS. Materials and methods: This retrospective study was performed on 80 AIS patients who had whole spine frontal and lateral radiographs, and the imaging parameters were measured and analyzed. Results: The coronal trunk imbalance rate was 67.5%, the trunk offset direction was towards left in 65 cases and right in 15 cases, and the head offset direction was towards left in 66 cases and right in 14 cases. The sagittal trunk imbalance rate was 57.25%. The distance of apical vertebrae and head offset in the coronal trunk balance group was significantly (P < 0.05) smaller than that in the imbalance group. The apical vertebrae offset distance and head offset distance were positively correlated with the tilt angle of trunk (r = 0.484 and 0.642, respectively, P < 0.05). The difference in the percentage of pressure load on the left and right foot was significantly (P<0.05) greater in the coronal imbalance group than that in the balance group.The center of pressure (COP) sway area was significantly (P< 0.05) larger in the overall trunk imbalance group (both coronal and sagittal imbalance) than in the balanced group. Conclusion: Most AIS patients have trunk imbalance which is severer on the coronal than on the sagittal plane. AIS patients with trunk imbalance show more significant local deformities, greater head offset, greater COP sway area, and decreased head and standing stability.